The prevailing thinking styles among sixth grade students in light of some variables "a field study in the schools of the city of hama" (Journal of Hama University, 2024)
The current research aimed to reveal the prevailing thinking styles among sixth grade students and their relationship to some variables (gender, father’s academic qualification), and used the descriptive analytical method. A sample consisting of (100) male and female students was chosen, chosen according to a random method, and an instrument scale was used. The research consists of (59) items and the research reached the following results:- The degree of agreement for the scale as a whole was high, with an average of (3.66). The universal method was the most preferred method among the students, and the legislative method came in last place.- There are no statistically significant differences among sample members on the scale according to the gender variable.- There are statistically significant differences on the total score of the questionnaire and on its dimensions (critical style, liberal style, hierarchical style) depending on the variable of the father’s academic qualification in favor of graduate studies.
Keywords: thinking methods; sixth grade students; Hama city